Implementing the Integrated Climate Data Analysis through Hands on Experiments and Jigsaw Methodology to Enhance the Attainment of Learning Outcomes in the Climate-Responsive Architecture Course in Architectural Education - Vidhyasankari, S. M.; Chandramathy, I. (Journal of Engineering Education Transformations, 2025)
As climate change poses unprecedented challenges to the built environment, architectural education must adapt to equip future architects with the necessary knowledge and skills to design climate-responsive buildings. This research explores the implementation of an innovative pedagogical approach in the climate-responsive architecture course, aimed at enhancing student’s learning outcomes through the integration of climate data analysis, hands-on experiments, and the jigsaw methodology. The study focuses on a cohort of architecture students engaged in a semester-long course specifically designed to address climate-responsive architectural concepts and principles. The results suggest that the integrated approach significantly improves student’s comprehension of climate-responsive architectural design principles and their ability to apply these principles to real-world design scenarios. The hands-on experiments and collaborative learning encourage participation, critical thinking, and creativity, while the jigsaw methodology encourages an interdisciplinary understanding of varied climate scenarios.The findings of this study contribute to the ongoing discourse on innovativeteaching methodologies in architectural education and provide valuable insights into the integration of climate-responsive design principles. By cultivating a generation ofarchitects equipped with climate-responsivedesign skills, architectural education can effectivelycontribute to mitigating the impacts of climate change and creating sustainable built environments for the future.